FISCALIZATION REFORM IN ALBANIA: AN ECONOMETRIC APPROACH TO STATE BUDGET REVENUES FROM FISCALIZED ENTERPRISES - Denisa CANI; Rezear KOLAJ; Petar BORISOV (Scientific papers series "management, economic engineering in agriculture and rural development", 2023)
The items that include public revenues in the state budget are very important for the economy, public expenditures, sustainability and growth depend on them. The functioning of the fiscal system in Albania has been particularly complicated for an important branch of the economy such as agriculture. It contributes approximately 18.4% to GDP, including 30% of employees. The Albanian government (January 1, 2021) started the implementation of the fiscalization platform, with the aim of collecting taxes in a more transparent way, especially the value–added tax, as one of the most difficult taxes to collect. Fiscalization represents a new digitized system of real–time reporting of the VAT situation for taxpaying subjects. The new innovative practice represents a comprehensive reform, especially in the field of issuing invoices, with an impact on taxpayers' income and the tracking of expenses. Considering the research gap, the study provides a general evaluation of the effects of fiscalization on the revenues collected from VAT, through an econometric approach. The results of the measurement (so far), show that the new fiscalization platform applied has influenced the increase in the number of businesses registered with a Unique Taxpayer Identification Number, formalizing the work of the majority of them. While the reform offers a positive development for public finances and in accordance with EU standards, a new continuous innovative approach in assisting new practices, logistics and the sustainability of management systems (cyber security) is recommended.